The Correlation between Tri Hita Karana's Implementation and Life Quality of Heart Failure Patients - Ida Ayu Agung Laksmi; Putu Wira Kusuma Putra; Ayu Made Budihartini (Babali Health, 2021)
Introduction: The quality of life of patients with heart failure is influenced by several factors, one of which is spiritual factors. Tri Hita Karana (THK) is one of the concepts of the life order of the Balinese people, which basically teaches about maintaining harmony between humans and God (prahyangan), humans and humans (pawongan), humans with the environment (palemahan). This study aimed to determine the relationship between THK implementation on the quality of life of heart failure patients at Regional Hospital of Mangusada. Methods: A cross-sectional design study was used. In total 41 heart failure patients who visited Mangusada Hospital between April to May 2020, selected using a purposive sampling technique. The research instrument used was the attitude and behavior implementation of THK and the Minnesota Living with Heart Failure Questionnaire (MLHFQ). The Spearman rank test was used in this study. Results: There were a significant correlation between Tri Hita Karana's Implementation and Life Quality of Heart Failure Patients in Mangusada Regional Hospital with p-value (0.001), where p < α (0.05). Conclusion: The better the implementation of THK, the better the quality of life for patients with heart failure. The results of this study were expected to be used in providing education to patients by implementing THK to improve the quality of life for patients with heart failure.